Anxiolytic Activity Of Tabernaemontana Divaricata (Linn.) R. Br. Flower Extract In Mice. - P. BASAVARAJ; B. SHIVAKUMAR; H. SHIVAKUMAR (International Journal of Pharma and Bio Sciences, 2011)
The present study was undertaken to evaluate anxiolytic activity of alcoholic flowers extract of Tabernaemontana divaricata (Linn) R.Br. (ALETD) by using mice. This plant contains carbohydrates, steroids, tannins, triterpenes, flavonoids, proteins, amino acids and glycosides. Anxiolytic effect of ALETD (100, 200 and 400 mg/kg) was studied and diazepam used as a standard drug by using following animal models, Elevated Plus Maze (EPM), Open-Field Test (OFT) and Light-Dark Transition Test (LDT). On EPM, the diazepam and all the doses of extract had showed significant anxiolytic activity by increasing open arm entries and time spent in open arm. In OFT increased total locomotion, central locomotion and decreased number of rearings, immobility time was observed with diazepam and all the doses of extract. In LDT model the anxiolytic activity was observed with diazepam as well as all the doses of extract by increasing latency, number of crossings, time spent in light box and decreasing rearings in light box was observed. The alkaloids, flavonides and other chemical constituents present in ALETD are speculated to account for the observed pharmacological effects of the plant’s extract in the experimental animal paradigms used. The findings of this experimental animal study indicate that ALETD possess anxiolytic property and thus lend pharmacological credence to the folkloric and ethanomedical uses of the plant in the treatment of anxiety condition.